Experiential learning to advocacy: A peer-led approach to safe medication disposal in pharmacy education - Jia Jia Lee; Li Ling Yeap; Ali Haider Mohammed; Chuan Sheng Yap; Bassam Abdul Rasool Hassan; Juman Abdulelah Dujaili; Pui San Saw; Ali Qais Blebil (PLoS ONE, 2026)
Introduction Safe medication disposal is crucial for public health and environmental sustainability, yet public awareness remains limited. While educational campaigns exist, pharmacy students can serve as key advocates in promoting proper disposal practices. This study integrates experiential learning and peer-led education to enhance students’ advocacy skills. Methods A two-phase mixed-method approach was used. In Phase 1, 35 pharmacy student ambassadors underwent hands-on training at community pharmacies, actively participating in medication take-back programs. Their experiences were documented and analyzed thematically. In Phase 2, they conducted a peer-led workshop for 43 undergraduate pharmacy students. A pre- and post-test assessed knowledge improvement among workshop participants. Results The thematic analysis identified five key themes: increased awareness, recognition of environmental and health risks, sense of responsibility, motivation for advocacy, and challenges in promoting safe disposal. Knowledge among workshop participants significantly improved, increasing from mean score 6.86 to 8.44 (Z = −4.827, p < 0.001), demonstrating the effectiveness of peer-led education. Conclusion Experiential learning combined with peer-led education effectively strengthened pharmacy students’ knowledge and advocacy for safe medication disposal. Engaging students as educators not only enhanced their own competencies but also improved awareness among peers. This approach empowers future pharmacists to advocate for responsible disposal practices within their communities.